Estudio del comportamiento del consumidor de los servicios de turismo en la ciudad de Machala - Reyes Tacuri, Geannina Janneth (2015)
Today tourism is growing stage for the great customer demand, so much so that the government policies promoting their participation in state tourism throughout Ecuador, still opportunity for tourism businesses to encourage new forms of tourism in the city, so that motivate the customer to purchase such services. With research of consumer behavior in tourism, tastes and preferences are diagnosed every tourist, depending on the areas or areas you visit for recreation; there are key factors influencing the purchase of tourist services such as effective information, customer service, quality of service, security, all these factors are reasons that drives consumer behavior research so that you get real data about the tastes or customer preferences, making the right decisions based on the design of strategic plan that will help the companies dedicated to this activity to implement these strategies for the development of your company.